Carbon Removal Using Coastal Blue Carbon Ecosystems Is Uncertain and Unreliable, With Questionable Climatic Cost-Effectiveness - Williamson, Phillip; Gattuso, Jean-Pierre (Frontiers in Climate, 2022)
Mangrove forests, seagrass meadows and tidal saltmarshes are vegetated coastal ecosystems that accumulate and store large quantities of carbon in their sediments. Many recent studies and reviews have favourably identified the potential for such coastal ‘blue carbon’ ecosystems to provide a natural climate solution in two ways: by conservation, reducing the greenhouse gas emissions arising from the loss and degradation of such habitats, and by restoration, to increase carbon dioxide drawdown and its long-term storage. The focus here is on the latter, assessing the feasibility of achieving quantified and secure carbon removal (negative emissions) through the restoration of coastal vegetation. Seven issues that affect the reliability of carbon accounting for this approach are considered: high variability in carbon burial rates; errors in determining carbon burial rates; lateral carbon transport; fluxes of methane and nitrous oxide; carbonate formation and dissolution; vulnerability to future climate change; and vulnerability to non-climatic factors. Information on restoration costs is also reviewed, with the conclusion that costs are highly uncertain, with lower-range estimates unrealistic for wider application. CO2 removal using coastal blue carbon restoration therefore has questionable cost-effectiveness when considered only as a climate mitigation action, either for carbon-offsetting or for inclusion in Nationally Determined Contributions. Many important issues relating to the measurement of carbon fluxes and storage have yet to be resolved, affecting certification and resulting in potential over-crediting. The restoration of coastal blue carbon ecosystems is nevertheless highly advantageous for climate adaptation, coastal protection, food provision and biodiversity conservation. Such action can therefore be societally justified in very many circumstances, based on the multiple benefits that such habitats provide at the local scale.